Performance of xenogeneic pulmonary visceral pleura as bioprosthetic heart valve cusps in swine - Lu, Xiao; Kelley, Greg; Wang, Mengjun; Guo, Xiaomei; Han, Ling; Kassab, Ghassan S. (Frontiers in Cardiovascular Medicine, 2023)
Objective Bovine pericardium is common biological material for bioprosthetic heart valve. There remains a significant need, however, to improve bioprosthetic valves for longer-term outcomes. This study aims to evaluate the chronic performance of bovine pulmonary visceral pleura (PVP) as bioprosthetic valve cusps. Methods The PVP was extracted from the bovine lung and fixed in 0.625% glutaraldehyde overnight at room temperature. The PVP valve cusps for the bioprosthetic valve were tailored using a laser cutter. Three leaflets were sewn onto a nitinol stent. Six PVP bioprosthetic valves were loaded into the test chamber of the heart valve tester to complete 100 million cycles. Six other PVP bioprosthetic valves were transcardially implanted to replace pulmonary artery valve of six pigs. Fluoroscopy and intracardiac echocardiography were used for in vivo assessments. Thrombosis, calcification, inflammation, and fibrosis were evaluated in the terminal study. Histologic analyses were used for evaluations of any degradation or calcification. Results All PVP bioprosthetic valves completed 100 million cycles without significant damage or tears. In vivo assessments showed bioprosthetic valve cusps open and coaptation at four months post-implant. No calcification and thrombotic deposits, inflammation, and fibrosis were observed in the heart or pulmonary artery. The histologic analyses showed complete and compact elastin and collagen fibers in the PVP valve cusps. Calcification-specific stains showed no calcific deposit in the PVP valve cusps. Conclusions The accelerated wear test demonstrates suitable mechanical strength of PVP cusps for heart valve. The swine model demonstrates that the PVP valve cusps are promising for valve replacement.